CNS Involvement in HIV Infection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The neurological findings in 41 HIV-seropositive children are described from the Departments of Paediatric Neurology and Hematology and Oncology, Zentrum der Kinderheilkunde, Goethe Universitat, Frankfurt, Germany.